Physicochemical characterisation of reduced graphene oxide for conductive thin films12. Issue 65 (7th November 2018) - Legge, Elizabeth J.; Ahmad, Muhammad; Smith, Christopher T. G.; Brennan, Barry; Mills, Christopher A.; Stolojan, Vlad; Pollard, Andrew J.; Silva, S. Ravi P.
Abstract : We introduce a combined process for the reduction of graphene oxide (GO) via vitamin C (ascorbic acid) and thermal annealing. Abstract : Graphene is a desirable material for next generation technology. However, producing high yields of single-layer flakes with industrially applicable methods is currently limited. We introduce a combined process for the reduction of graphene oxide (GO) via vitamin C (ascorbic acid) and thermal annealing at temperatures of <150 °C for times of <10 minutes, resulting in electrically conducting thin films with sheet resistances reducing by 8 orders of magnitude to as low as ∼1.3 kΩ □ −1, suitable for microelectronics, display technology and optoelectronic applications. The in-depth physicochemical characterisation of the products at different stages of GO preparation and reduction allows for further understanding of the process and demonstrates the suitability for industrial production methodologies due to an environmentally-friendly reducing agent, solution processability and no requirement for high temperatures. The presence of the vitamin C lowers the temperature required to thermally reduce the GO into an electrically conducting thin film, making the technique suitable for thermally sensitive substrates, such as low melting point polymers. Simultaneous spray coating and reduction of GO allows for large area deposition of conductive coatings without sacrificing solution processability, often lost through particle agglomeration, making it compatible with industrial processes, and applicable to, for example, the production of sensors, energy devices and flexible conductive electrodes for touchscreens.